S32 Characterising school-age children with asthma: English population-cohort study. (11th November 2022) - Khalaf, Z; Saglani, S; Bloom, CI
Abstract : Introduction and Objectives: There is currently little information regarding the clinical characteristics of English school-aged children at the time of their asthma diagnosis. We conducted a nationwide study to determine and compare baseline characteristics, subsequent asthma management and incidence of asthma attacks, by age of diagnosis. Methods: Descriptive analysis was performed using primary care electronic healthcare records (Clinical Practice Research Datalink) linked to Hospital Episode Statistics. The study population included children, aged 5–16 years with ≥2 asthma codes, 2004 to 2021. Children were categorised by age at diagnosis: 5–9, 9–12 and 12–16 years. Results: There were 166, 578 eligible children (83, 164 in 5–9 years, 45, 330 in 9–12 years, 38, 085 in 12–16 years). Of whom 59.7% males in 5–9 years compared to 48.5% in 12–16 years. Atopy was common in all age groups (57.3% of all children). Younger children had more eczema and older children had more allergic rhinitis ( figure 1 ). Within the first two years of diagnosis, most children were prescribed an inhaled corticosteroid (ICS), the highest proportion in the youngest children (86.4% of 5–9 years, 81.2% of 9–12 years, 77.6% of 12–16 years). The oldest age group received the highest proportion of reliever prescription alone (12.8% in 5–9 years, 18.2% in 9–12 years, 21.6% in 12–16 years). 11.4% of children received medium or high dose ICS, 58.2% of whom received this dose as their first ever ICS prescription. Within the first two years after diagnosis, 21.7% of all children had an asthma attack. The youngest children were most likely to have attacks and within the shortest time from diagnosis (25% had an attack by (years): 1.8=6–9 years, 3.7=9–12 years, 4.8=12–16 years). Conclusion: Boys were more likely to have asthma until around 12 years old, whereafter girls were more likely to. Just under half of the oldest children were overweight/obese. More than half of all children had atopy. Approximately 1 in 5 children had an asthma attack within 2 years of diagnosis, this was highest in children diagnosed between 5–9 years, despite highest ICS prescription rates. Inappropriate management on reliever alone was also prevalent, occurring in approximately 20% of children.